ANALISIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI DI KELAS X IPA SMA NEGERI 4 KISARAN TAHUN PEMBELAJARAN 2016/2017 - Helentina Helentina; Ahmad Shafwan S Pulungan; Arlina Sinaga (Jurnal Pelita Pendidikan, 2017)
The objective of this study is to know difficulties rate of students on biology subjects. This study isquantitative descriptive research. The sample was taken in total sampling involved comprising 34 students asGrade X IPA-1, another 34 students Grade X IPA-2, still 33 students grade X IPA-3, also 33 students Grade X IPA-4,and 31 students Grade X IPA-5. The instrument of provided questionnaire paper with 40 questions. The resultindicated that students got difficulties to study on each . The internal factor as causes go difficulties of students instudying known as factor of intelligence, attention of students, motivation, interest, health as well as. While,external factor cause the students got difficulties in studying seemly tool for learning, environmental, media,method/ strategic done by teacher, and parents.Keywords: learning difficulties